A Systematic Literature Review of Yusuf Al-Qaradawi’s Moderation Doctrine: Strategies for Enhancing Campus Harmony at Universiti Utara Malaysia - Muhamad Rizza; Asep Nursobah (UIN Sunan Gunung Djati Bandung, 2024)
Specifically, this study examines Yusuf Al-Qaradawi’s notion of religious moderation and its contribution to tolerance and interfaith relations at the Universiti Utara Malaysia. This study explores the concept of moderation in religion in a detailed and thorough literature review. Based on the analysis of Al-Qardhawi's writings and qualitative research designs, this research finds that to create a respectful climate between groups and individuals fully dedicated to their veneration but mentally moderate towards each other who could afford greater coexistence relied on integrating religious moderation in line with educational policy and curriculum implementation. The anticipated benefits of these initiatives include: educating students in the practice of respectful discussion across faith traditions; advancing a climate of greater inclusivity on campus â€“ both academically and socially; and encouraging a more constructive faculty-student engagement concerning the religious diversity among our student body. This study seeks both findings and recommendations by identifying additional steps that institutions may take in areas of governance, policy and student services to embrace the value of religious diversity. Increased interfaith dialogue and enhanced social cohesion among students, faculty, and staff will provide additional benefits to the university community that implementation of these recommendations is anticipated to produce. Qualitative research methods will be designed to identify actionable insights and findings on which we can further promote religious tolerance and inclusivity. The findings would lead to the next steps of making further improvements in religious moderation at educational institutions, to create a more harmonious and respectful academic atmosphere.